Learning experience design for augmented reality - Betül Czerkawski; Margherita Berti (Association for Learning Technology, 2021)
Recent years have seen a growing interest in augmented reality (AR) technologies due to their potential for simulating real-life situations and creating authentic learning tasks. Studies have shown that AR enables engaging and interactive learning experiences (e.g. Bressler and Bodzin 2013; Klopfer and Sheldon 2010) and can benefit student learning (e.g. Bonner and Reinders 2018; Siegle 2019). However, although research in AR for education is not scarce, educators often do not have a learning experience design (LXD) approach that is supported by the recent findings of learning sciences and instructional design models. To bridge this gap, the present study introduces an AR-learning prototype developed by using SAM I (Successive Approximation Model I), and the Threshold Concepts Framework, employed for meaningful integration of AR into the learning process. A pre-survey and a post-survey method were utilised in the data gathering process to gauge students' experience with the AR module. The findings show that the majority of students have not had educational experiences with AR prior to the study, and they struggled to find ways to incorporate this technology into their content areas in a meaningful way. Nonetheless, participants realised the value of AR and stated that they most likely would use this technology in the future. Based on the findings, the authors present a set of suggestions for instructors and LXDs, and provide recommendations for future research.